REPRESENTASI OBJEKTIFIKASI PEREMPUAN DALAM FILM SELESAI (ANALISIS SEMIOTIKA ROLAND BARTHES) - Freshia Trinanda Hamid; Sunarto Sunarto; Lintang Ratri Rahmiaji (Interaksi Online, 2023)
Film productions in Indonesia still present characterizations that are attached to traditional gender constructions and objectify the female body. The director of “Selesai” stated that this movie is produced as a form of his perception regarding the patriarchal culture in Indonesia, presenting social facts, starting a new perspective, and not discrediting women. Based on the director's statement, this study aims to describe the objectification of women and find the dominant ideology in the text. The main theory used is standpoint theory, supported by male gaze theory, radical libertarian feminism, and the concept of objectification of NussbaumLangton. The method used is the semiotic analysis of Roland Barthes (5 codes). The main finding of this research is that “Selesai” represents the objectification of women, where the objectification is carried out by men, fellow women, and women themselves. Referring to the concept of Nussbaum Langton, some forms of objectification found in the movie; Instrumentality, where women are used as tools to satisfy men's sex that is represented in the movie through mistresses, girlfriends, and even in imagination, used as money-making tools and seen as instruments that should give birth in marriage relations. Denial of autonomy and inertness, a restriction on women when they try to make decisions for themselves such as husbands who refuse to divorce, women who have no autonomy to determine whether to give birth and are admitted to mental hospitals. Ownership can be seen from the unequal ownership relations where men tend to be dominant in both dating and marriage relationships and “playing victim” practices to justify the commitment violations. Fungibility, women can be exchanged if she didn’t meet expectations. Violability, women as objects who can be treated harshly, to be hurt, their rights are fine to be robbed, cheated on, and bullied verbally and non-verbally. Denial of subjectivity, women's experiences, and feelings are ignored. Reduction of appearance, women's value is reduced based on their appearance and reduction of the body where there is a focus on women through how the camera works on certain body parts. The objectification in “Selesai” is accompanied by a lack of female resistance, this emphasizes the dominant ideology of patriarchy and contradicts the director's statement which says that this movie didn’t discredit women because the facts chosen in this movie aren’t constructed well with gender equality. Based on the results of this critical research, it’s inaccurate if the contents of the film are used as material for a reflection to change society.